Reaching Consensus with VICA-ELECTRE TRI: A Case Study - Bezerra, Francineide de Morais (2017)
This paper reports on an application of the VICA-ELECTRE TRI to a real world case study. We used the model VICA (Visual, Interactive and Comparative Analysis of individual opinions) to aid a cooperative group achieving a collective solution to a multicriteria sorting problem (student allocation to classes on a language school). Based on the individual results initially obtained, the model provides tools for the visualization of results and their comparison. It also points out means to seek or build a consensus on a solution, by guiding the changes of parameters and/or preference revisions in different possible ways of interaction between the members of the group. After a brief description of the model, we present the procedures followed, from the meeting plan to the case analysis.